Pharmacokinetics, Safety, Tolerability, and Pharmacodynamics of Alicapistat, a Selective Inhibitor of Human Calpains 1 and 2 for the Treatment of Alzheimer Disease: An Overview of Phase 1 Studies. Issue 3 (27th July 2018) - Lon, Hoi‐Kei; Mendonca, Nuno; Goss, Sandra; Othman, Ahmed A.; Locke, Charles; Jin, Ziyi; Rendenbach‐Mueller, Beatrice
Abstract: Alicapistat is an orally active selective inhibitor of calpain 1 and 2 whose overactivation has been linked to Alzheimer disease (AD). Three studies were conducted in healthy subjects (18‐55 years), 1 in healthy elderly subjects (≥65 years), and 1 in patients with mild to moderate AD. Four studies assessed pharmacokinetics, 1 study in healthy subjects assessed pharmacodynamics (sleep parameters, particularly rapid eye movement [REM], as a measure of central nervous system [CNS] penetration and activity), and all studies assessed safety. Participants received single doses or multiple twice‐daily doses of alicapistat for up to 14 days. Maximum alicapistat plasma concentrations were reached in 2 to 5 hours; half‐life was 7 to 12 hours postdose. Alicapistat exposure was dose proportional in the alicapistat 50‐ to 1000‐mg dose range. Exposure of the alicapistat R, S diastereomer was approximately 2‐fold greater than exposure of the R, R diastereomer in healthy young and elderly subjects and patients with AD. Alicapistat at 400‐ or 800‐mg twice‐daily doses had no effect on REM sleep parameters, whereas the active control, donepezil at 10 mg twice daily, affected sleep parameters. Across all trials, the incidence of treatment‐emergent adverse events was similar in the placebo and alicapistat groups. There were no clinically significant changes in vital signs and laboratory measurements. The lack of an effect of alicapistat on sleep suggests that concentrations in the CNS were inadequate or that preclinical studies do not predict alicapistat effects in humans.